Applying Constructionist Approaches to Teaching English Argument Structure Constructions to EFL Learners. Issue 2 (20th October 2020) - Kim, Hyunwoo; Rah, Yangon
Abstract : The present study investigated the effects of construction‐based instruction on Korean English as a foreign language (EFL) learners' production of the English argument structure constructions. Within the theoretical framework of construction grammar (Goldberg, 1995), the authors presented college students with English constructions in a hierarchical network and provided contextually meaningful visual scenes in connection with the language input. Results from translation and guided writing tasks, which were implemented before, immediately after, and 4 weeks after the learning sessions, revealed that learners who received construction‐based instruction outperformed those who received form‐centered instruction in both immediate and delayed posttests. Further, among the construction‐based groups, only those learners who were presented with the target constructions in a network hierarchy maintained improved performance in the delayed posttest. The authors conclude by addressing the pedagogical implications for construction‐based teaching in the EFL context. Abstract :